PATHOMORPHOLOGICAL CHANGES OF THE SKELETAL MUSCLES UNDER FORMATION OF THE REPERFUSION SYNDROME - Anisimova, L V; Kubyshkin, A V; Aliev, L L; Bessalova, Ye Yu; Kharchenko, V Z (T͡S︡itologii͡a, 2017)
Analysis of pathomorphological changes which taking place in muscle tissue after reperfusion of previously ischemic rats limbs allowed to identify three phases of the experimental reperfusion syndrome (RS): the first or ischemic, the second or initial reperfusional, the third or late reperfusional. Morphological changes of the skeletal muscles in the first stage are characterized by presence of dystrophic-necrotic processes and reflect the compensatory-adaptive reaction of the organism to hypoxia. In the third stage one can see the progress of morphological damages, which develop during the ischemic period against a background of exhaustion of proteinase inhibitors. This indicates the intensity of endogenous intoxication of the organism with the products of disturbed metabolism and determines the irreversibility of destructive processes and probability of multiple organ failure. Proceeding from the character of the pathomorphological changes and the state of proteinase-inhibitor system one can suppose, that the optimal time for medical measures is the first stage and the first hours of the second stage (to increase the ischemic tolerance of the skeletal muscles). Taking into account the direct relation between the intensity of pathomorphological injuries and the imbalance of proteinase-inhibitor system, the usage of proteinase-inhibiting medicines for correction of RS-development and reduction of the destructive changes during first and second stages is substantiated. When reperfusion syndrome lasts for a long time, medical measures become ineffective due to the high degree of pathological changes.